Negosiasi Syariat dan Konstitusi: Konfigurasi Politik Hukum Terhadap Formalisasi Hukum Jinayat Aceh - M. Ridho Ilahi (UIN Syarif Hidayatullah Jakarta, 2025)
This article examines the formalization of Jinayat law in Aceh within the relationship between Islamic law and the Indonesian constitution by positioning it as a product of legal-political negotiation in the post-conflict Aceh context. Using a qualitative method with a historical-normative approach, this study analyzes constitutional provisions, statutory regulations on Aceh’s special autonomy, Jinayat qanun, and relevant socio-political dynamics following the Aceh conflict. The findings demonstrate that the formalization of Jinayat law was shaped by a responsive legal-political configuration after the Reform era, functioning not merely as the execution of constitutional mandates but also as a political instrument for conflict resolution, democratization, and national integration. By mapping the interaction between central and regional political interests, religious authority, and local socio-cultural legitimacy, the study shows that Jinayat law emerged through negotiation rather than unilateral constitutional enforcement. The novelty of this research lies in its argument that the Jinayat legal regime in Aceh represents a form of responsive legal politics, where constitutional recognition of regional special status intersects with pragmatic political considerations in post-conflict governance. This study contributes to political-legal scholarship by offering a nuanced understanding of Islamic law formalization as a dynamic constitutional and political process that must remain aligned with democratic principles and constitutional values.